Pengaruh Penerapan Sistem Moving Class Dan Keterampilan Kolaborasi Siswa Terhadap Hasil Belajar Siswa Ekonomi Fase F Di SMA Negeri 8 Padang - Alias Zalogo; Reni Respita; Widya Astuti (JURNAL ARMADA PENDIDIKAN, 2025)
This study aims to determine how much: (1) the application of the moving class system influences the learning outcomes of phase F economics students at SMA Negeri 8 Padang, (2) the influence of students' collaboration skills on the learning outcomes of phase F economics students at SMA Negeri 8 Padang, (3) the influence of the application of the moving class system and students' collaboration skills on the learning outcomes of phase F economics students at SMA Negeri 8 Padang.This study used a quantitative method. The population in this study was 200 economics students of phase F with a sample size of 126 students. Sampling in this study used purposive sampling, namely selecting classes according to research criteria by examining classes with an incompleteness rate of ˃ 50%.The results of this study indicate (1) the application of the moving class system has a positive and significant effect on the learning outcomes of economics students in phase F at SMA Negeri 8 Padang with a t-count value of 3.221 ˃ 1.980 with a significance level of 0.002 < 0.05. (2) There is a positive and significant effect of collaboration skills on learning outcomes with a t-count value of 2.291 ˃ 1.980 with a significance level of 0.024 < 0.05. (3) There is a simultaneous effect of the application of the moving class system and student collaboration skills on the learning outcomes of economics students in phase F at SMA Negeri 8 Padang, with an F-count value of 9.087 ˃ F-table of 3.070 and significant at 0.000 < 0.05